Chemical constituents from the twigs, fruits and roots of cratoxylum cochinchinense and antioxidation properties - Suthida Rattanaburi (Prince of Songkla University, 2007)
Thesis (M.Sc., Organic Chemistry)--Prince of Songkla University, 2007